Molecular Ligand‐Mediated Assembly of Multicomponent Nanosheet Superlattices for Compact Capacitive Energy Storage. (2nd September 2020) - Wu, Guanhong; Li, Tongtao; Wang, Zhilei; Li, Mingzhong; Wang, Biwei; Dong, Angang
Abstract: Inspired by the self‐assembly of nanoparticle superlattices, we report a general method that exploits long‐chain molecular ligands to induce ordered assembly of colloidal nanosheets (NSs), resulting in 2D laminate superlattices with high packing density. Co‐assembly of two types of NSs further enables 2D/2D heterostructured superlattices. As a proof of concept, co‐assembly of Ti3 C2 T x and graphene oxide (GO) NSs followed by thermal annealing leads to MXene‐rGO superlattices with tunable microstructures, which exhibit significantly higher capacitance than their filtrated counterparts, delivering an ultrahigh volumetric capacitance of 1443 F cm −3 at 2 mV s −1 . Moreover, the as‐fabricated binder‐free symmetric supercapacitors show a high volumetric energy density of 42.1 Wh L −1, which is among the best reported for MXene‐based materials in aqueous electrolytes. This work paves the way toward rational design of 2D material‐based superstructures for energy applications. Abstract : A strategy of building compact 2D/2D superlattice films based on molecular ligand‐mediated assembly of colloidal nanosheets is presented. Thanks to their densely packed nature and high stacking ordering, co‐assembled MXene‐rGO laminate films exhibit arguably the highest volumetric energy density ever reported for MXene‐based supercapacitors in aqueous electrolytes.